Effect of Regional Tax, Population, and GRDP on Original Local Government Revenue (PAD) in the Regency/City of Central Java Province - Nisa, Zulfatun; Bahari, Fitri (Jurnal Samudra Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of taxes, population, and GRDP on local revenue (PAD) in Central Java Province in 2013-2019. The data panel with the fixed effect method was run to analyze the data using the help of the EViews v.11 program. Objects are 35 regencies/cities in Central Java Province. The dependent variable is Regional Original Income (PAD); while district/city taxes in Central Java Province, total population, and GRDP are independent variables. The results of this study indicate that taxes and GRDP have a positive and significant effect on PAD, while population has a positive but not significant effect on PAD in Central Java Province.